Pharmacogenetics of FSH Action in the Female - Conforti, Alessandro; Vaiarelli, Alberto; Cimadomo, Danilo; Bagnulo, Francesca; Peluso, Stefania; Carbone, Luigi; Di Rella, Francesca; De Placido, Giuseppe; Ubaldi, Filippo Maria; Huhtaniemi, Ilpo; Alviggi, Carlo (Frontiers in Endocrinology, 2019)
The purpose of a pharmacogenomic approach is to tailor treatment on the basis of individual human genotype. This strategy is becoming increasingly common in medicine, and important results have been obtained in oncologic and antimicrobial therapies. The rapid technological developments and availability of innovative methodologies have revealed the existence of numerous genotypes that can influence the action of medications, and that a true “individualized” approach could become in the future a reality in clinical practice. Moreover, comparing with the past, genotype analyses are now more easily available at accessible cost. Concerning human reproduction, there is ample evidence that several variants of gonadotropins and their receptors influence female reproductive health and ovarian response to exogenous gonadotropins. In more detail, variants in genes of follicle-stimulating hormone β-chain (FSH-B) and its receptor (FSH-R) seem to be the most promising candidates for a pharmacogenomic approach to controlled ovarian stimulation in assisted reproductive technologies. In the present review, we summarize the evidence regarding FSH-B and FSH-R variants, with special reference to their impact on reproductive health and assisted reproductive technology treatments.